Development and maturation of fruits of two indupalma oxg hybrids (elaeis oleifera x elaeis guineensis) (2013)
OxG hybrids are materials with characteristics notable fortolerance to pests and diseases, high quality oil and acceptablebunch production, but the physiological processes of growthand maturation of the fruits are not well known. For the twohybrid materials (Coarí x La Mé and Sinú-Coarí x La Mé), thephysiological and biochemical changes during the growth andmaturation of the bunches were studied in San Alberto, Cesar(Colombia) with a climate of 2,497 mm/year precipitation and27°C. Female inflorescences in anthesis were selected and thechanges in size, color, and oil content of the external, internaland red parthenocarpic fruits of the bunches were recordedfrom 98 days after anthesis (DAA). A completely randomexperimental design was used with five replications and 13sample dates. In hybrid Coarí x La Mé, 70% of the oil in thefruits accumulated between 98 and 126 DAA and reached themaximum at 168 DAA, while in hybrid Sinú-Coarí x La Mé,more than 90% of the oil accumulated between 98 and 140DAA, also reaching the maximum at 168 DAA. The external,internal and red parthenocarpic fruits of the bunches reachedthe maximum percentages of oil/dry mesocarp at the sametime (day). It is possible to estimate the percentage of oil/moistmesocarp based on the moisture percentage of fresh fruits.